Regulatory differences and international financial integration - Tatsiana Kliatskova (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The Capital Markets Union (CMU) - an initiative of the European Commission - aims to unify and deepen capital markets across EU Member States by removing existing barriers to cross-border investment and, in particular, harmonizing financial and business regulations. However, harmonizing institutional frameworks across the EU Member States that historically have different legal traditions is difficult and requires time. This article summarizes important steps to harmonizing business and financial laws in the EU and discusses empirical and theoretical literature on the role of legal harmonization in deepening and better integrating financial markets.
Keywords: 330